FFT-Size Efficient 4096-QAM OFDM for Low-Cost DML-Based IMDD System - Qinghui Chen (IEEE Photonics Journal, 2016)
In this paper, we have experimentally demonstrated the transmission of the 4096-quadrature amplitude modulation (4096-QAM)-encoded optical orthogonal frequency division multiplexing (OFDM) signals in a low-cost directly modulated laser (DML)-based intensity-modulated and direct-detection (IMDD) optical communication system. To the best of our knowledge, it is the first time the highest QAM and fast fourier transform (FFT) size efficient OFDM signal with a spectral efficiency up to 9.5 bit/s/Hz transmissions over a DML-based IMDD system has been reported. The experimental results show that the 4096-QAM OFDM signal can be successfully transmitted over 10-km standard single-mode fiber (SSMF) with a bit error rate (BER) below the 20% overhead soft-decision forward error correction threshold (SD-FEC). It also shows that the FFT-size efficient optical 4096-QAM OFDM has the same BER performance as the conventional one. Moreover, the effect of laser phase noise (or linewidth) on the transmission performance of the FFT-size efficient 100G 4096-QAM-OFDM is also investigated by numerical simulation. The simulation shows that the optical 100G OFDM signals generated by 10G DML with a linewidth of 20 MHz can be successfully transmitted over 2 km SSMF with the BER under the SD-FEC threshold of 2.4 × 10-2.